Modified Genetic Algorithm with Flexible Crossover for the Capacitated Electric Vehicle Routing Problem - Ajchara Phu-ang; Arit Thammano (My University, 2023)
This paper proposed a modification of genetic algorithm with a new technique called the flexible crossover operation for solving the capacitated electric vehicle routing problem (CEVRP). The framework of this paper is based on the concept of the classic genetic algorithm (GA). To improve the performance of the genetic algorithm, two aspects have been proposed, 1) The Pre-Post mutation is present to obtain the ability of local search capacities. 2) The flexible crossover operation is proposed to enhance the diverse capabilities. The proposed algorithm has been evaluated and compared to the state-of-the-art algorithms. The experimental result on seven data sets demonstrated that the proposed algorithm is effective for solving a small and medium data set of capacitated electric vehicle routing problem.
Keywords: Vehicle Routing Optimization Methods; Metaheuristic Optimization Algorithms Research; Advanced Multi-Objective Optimization Algorithms